Rapid Detection of Nocardia by Next-Generation Sequencing - Weng, Shan-Shan; Zhang, Han-Yue; Ai, Jing-Wen; Gao, Yan; Liu, Yuan-Yuan; Xu, Bin; Zhang, Wen-Hong (Frontiers in Cellular and Infection Microbiology, 2020)
In this original study, we retrospectively reviewed the cases of nocardiosis diagnosed through culture and next-generation sequencing (NGS) methods between 2014 and 2018 in Huashan Hospital and found out that the latter way can not only improve the detection rate of Nocardia spp. but also greatly reduce the turnaround time. In addition, by comparing nocardiosis and non-nocardiosis patients both of whose samples had Nocardia spp. detected by NGS, we found that Nocardia's specific reads ranking among top two might be a satisfactory cutoff value for clinical diagnosis of the disease. Our study introduced the promising value of the NGS method in the rapid diagnosis of nocardiosis.